In vivo characterization of downfield peaks at 9.4 T: T2 relaxation times, quantification, pH estimation, and assignments. Issue 2 (11th August 2020) - Borbath, Tamas; Murali‐Manohar, Saipavitra; Wright, Andrew Martin; Henning, Anke
Abstract : Purpose: Relaxation times are a valuable asset when determining spectral assignments. In this study, apparent T2 relaxation times ( T 2 app ) of downfield peaks are reported in the human brain at 9.4 T and are used to guide spectral assignments of some downfield metabolite peaks. Methods: Echo time series of downfield metabolite spectra were acquired at 9.4 T using a metabolite‐cycled semi‐LASER sequence. Metabolite spectral fitting was performed using LCModel V6.3‐1L while fitting a pH sweep to estimate the pH of the homocarnosine (hCs) imidazole ring. T 2 app were calculated by fitting the resulting relative amplitudes of the peaks to a mono‐exponential decay across the TE series. Furthermore, estimated tissue concentrations of molecules were calculated using the relaxation times and internal water as a reference. Results: T 2 app of downfield metabolites are reported within a range from 16 to 32 ms except for homocarnosine with T 2 app of 50 ms. Correcting T 2 app for exchange rates ( T 2 c o r r ) resulted in relaxation times between 20 and 33 ms. The estimated pH values based on hCs imidazole range from 7.07 to 7.12 between subjects. Furthermore, analyzing the linewidths of the downfield peaks and their T 2 app contribution led to possible peak assignments. Conclusion: T 2 app relaxation times were longer for the assigned metabolite peaks compared to the unassigned peaks. Tissue pH estimation in vivo with proton MRS and simultaneous quantification of amide protons at 8.30 ± 0.15 ppm is likely possible. Based on concentration, linewidth, and exchange rates measurements, tentative peak assignments are discussed for adenosine triphosphate (ATP), N‐acetylaspartylglutamate (NAAG), and urea.